1307 IMPLEMENTING THE HEE COMPREHENSIVE GERIATRIC ASSESSMENT (CGA) FOR FALLS IN CARE HOME PATIENTS– A QUALITY IMPROVEMENT PROJECT. (16th January 2023) - Jones, K; Tekkis, N; Dronfield, S; Munslow, N
Abstract: Introduction: According to the Health Education England (HEE) Framework for Enhanced Health in Care Homes 2020, 33% of people over 65 and 50% of people over 80 have one or more fall a year, figures which significantly increase in care home residents. Prevention of falls promotes the quality of life of elderly patients and could significantly reduce the burden on primary and secondary care stemming from fall induced fractures, loss of mobility and community follow up. The Comprehensive Geriatric Assessment (CGA) for falls includes a full falls assessment questionnaire, medication review, lying/standing blood pressure and frailty index. The HEE set out a requirement that all care home patients should have a CGA assessment within 7 days of readmission to a care home following a hospital episode because of a fall. This audit examined the compliance of Four Counties primary care network (PCN) to the 7-day CGA HEE guideline for falls. Methods: Retrospective analysis of 68 eligible patients from Four Counties PCN between 31st March 2021 and 1st March 2022. Analysis indicated a poor compliance to the HEE CGA guidelines (15%). After presenting to the MDT, we formulated a system-wide plan to improve reporting of care home falls to OTs, creating protected time for pharmacists to conduct care home medication reviews and promoting in-person weekly care-coordinator meetings. The PCN was audited for a second time after 3 months. Results: A significant improvement (15% to 57%) in adherence to the HEE CGA framework was noted after implementation of above changes. Medication review in 7 days improved from 42% to 80% and falls assessment questionnaire in 7 days compliance improved from 23% to 70%. Conclusion: Creating clear protocols for reporting falls and clarifying MDT roles in the CGA are essential to identifying and preventing falls in at-risk care home residents.